PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR IPA KELAS IV SD NEGERI 021 BUNGA TANJUNG KECAMATAN RENGAT BARAT - Ikhwan '; Otang Kurniaman; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the fact that is found in the class IV SD Negeri 021 Bunga TanjungKecamatan Rengat Barat, which show the result of learning in IPA is still relatively low. Formulation the problem in this research is: Does the application of contextual teaching and learning (CTL) can improve learning outcomes in IPA studens of SD Negeri 021 Bunga Tanjung Kecamatan Rengat Barat?”. This research aims to improve learning otcomes in IPA students of SD Negeri 021 Bunga Tanjung Kecamatan Rengat Barat Kabupaten Indragiri Hulu with application of contextual teaching and learning (CTL). The hypothesis of this study is that if applied contextual teaching and learning (CTL) it can improve learning outcomes in IPA students of SD Negeri 021 Bunga Tanjung Kecamatan Rengat Barat Kabupaten Indragiri Hulu. This research was conducted in SD Negeri 021 Bunga Tanjung Kecamatan Rengat Barat in April 2016. This from research classroom action research (PTK) are planned as much as two cycle. The subject was students of class IV D Negeri 021 Bunga Tanjung Kecamatan Rengat Barat academic year 2015/2016 which amounted to 30 people consisting of 16 man and 14 women. Based on the results of research of teacher activity sheet seen rising each meeting. At the first meeting of the first cycle of 64,3%, the second meeting of the first cycle of 67,86%. At the first meeting of the second cycle of 71,43%, the second meeting of the second cycle of 78,57%. Students avtivity observation sheet also increased at every meeting. At the first meeting of the first cycle of 67,86%, the second meeting of the first cycle of 71,43%. At the first meeting of the second cycle of 75%, the second meeting of the second cycle of 78,57%. Mastery learning outcomes to repeat at first cycle increased 12,8% from the base score 67,83% to 76,5%. In the second cycle increased by 17,2% to 79,5%. So that research result are consistent with the hypothesis. Key words: contextual teaching, sains learning outcomes